ANALISIS PERBANDINGAN KINERJA KARYAWAN TETAP DENGAN KARYAWAN OUTSOURCING PADA PT SANGGAR SARANA BAJA TIMIKA - Rima Rima; Abu Bakar (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This study aims to determine the performance of permanent employees and outsourcing employees at PT Sanggar Sarana Baja Timika. To achieve this objective, the study employs a descriptive research method. The required data is collected through questionnaire surveys and observation techniques. Descriptive statistical analysis is used to analyze the research data, specifically the mean values that are operationalized according to the research needs. The results of the study indicate that the performance of permanent employees at PT Sanggar Sarana Baja Timika is higher compared to the performance of outsourcing employees. Furthermore, the analysis results highlight that the work quantity dimension is one of the most influential factors in the performance difference between permanent employees and outsourcing employees. Permanent employees at PT Sanggar Sarana Baja Timika demonstrate better work quantity compared to outsourcing employees.